A case of a resected benign myxoma-like hemorrhagic cyst, which later recurred as undifferentiated pleomorphic sarcoma in the left atrium. Issue 16 (April 2017) - Kim, Eunju; Choi, Seo-Won; Min, Daniel; Kim, Sang Hoon; Yang, Woo-In; Moon, Jae Youn; Sung, Jung Hoon; Kim, In Jai; Lim, Sang-Wook; Cha, Dong-Hun; Moon, Byung; Cho, Sang-Ho; et al.
Abstract: Rationale: An intracardiac cystic mass is a rare type of mass found in the left atrium. The differential diagnosis of an intracardiac cystic mass includes hydatid cysts, bronchogenic cysts, intracardiac varices, and hemorrhages in some tumor types, including myxoma. Patient concerns: We present the case of a 68-year-old woman who presented with episodic dyspnea. Diagnoses-Interventions-Outcomes: Transthoracic echocardiography (TTE) revealed the presence of a left atrial mass mimicking myxoma. However, in postoperative findings, it was determined that the mass was actually a hemorrhagic cyst. Eighteen months later, the patient presented with recurrent exertional dyspnea and TTE revealed the recurrence of a left atrial mass. Computed tomography showed that the mass extended into the right atrium, inferior vena cava, and coronary sinus. After re-operation, the final histological diagnosis was determined to be an undifferentiated pleomorphic sarcoma in the left atrium. Lessons: An intracardiac hemorrhagic cyst was suspected during the operation of a benign-looking LA mass. As such, we recommend that other rare etiologies be considered and more biopsies be performed when possible.